2021
DOI: 10.1007/s00787-021-01851-1
|View full text |Cite
|
Sign up to set email alerts
|

Perceived impact of the COVID-19 pandemic on child and adolescent psychiatric services after 1 year (February/March 2021): ESCAP CovCAP survey

Abstract: In April 2020, the European Society for Child and Adolescent Psychiatry (ESCAP) Research Academy and the ESCAP Board launched the first questionnaire of the CovCAP longitudinal survey to estimate the impact of COVID-19 on child and adolescent psychiatry (CAP) services in Europe. In this brief report, we present the main findings from the second questionnaire of the survey, one year after the COVID-19 pandemic began to hit Europe (i.e., February/March 2021). While service delivery to patients and their families… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 7 publications
2
33
0
2
Order By: Relevance
“…The observation of a delayed but alarming increase in treatment demand up to January/February/March 2021 was confirmed by the analysis of electronic patient records prior and during the COVID-19 pandemic from the emergency outpatient facility of the Department of Child and Adolescent Psychiatry and Psychotherapy in the Psychiatric University Hospital Zurich [ 20 ]. These findings also correspond to reports from some other European countries [ 8 , 9 ], although data on the number of outpatient treatments are not consistent. In a survey of European clinics for child and adolescent psychiatry, respondents more often indicated that the number of outpatients decreased (N = 21) rather than increased (N = 10) in February/March 2021, compared to before the pandemic [ 8 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The observation of a delayed but alarming increase in treatment demand up to January/February/March 2021 was confirmed by the analysis of electronic patient records prior and during the COVID-19 pandemic from the emergency outpatient facility of the Department of Child and Adolescent Psychiatry and Psychotherapy in the Psychiatric University Hospital Zurich [ 20 ]. These findings also correspond to reports from some other European countries [ 8 , 9 ], although data on the number of outpatient treatments are not consistent. In a survey of European clinics for child and adolescent psychiatry, respondents more often indicated that the number of outpatients decreased (N = 21) rather than increased (N = 10) in February/March 2021, compared to before the pandemic [ 8 ].…”
Section: Discussionsupporting
confidence: 84%
“…For spring 2020, only a small proportion of respondents (generally less than 30%) reported an increased prevalence occurrence of certain disorders, such as anxiety or obsessive compulsive disorders. By contrast, for February/March 2021, the vast majority of respondents reported increased numbers of cases with anxiety disorders (70%), depression (>60%), eating disorders (>60%), and suicidal crises (>80%) [ 8 ]. Data from the Republic of Ireland [ 9 ] indicate that referrals to specialized child and adolescent mental health services dropped by around 10% up to August 2020 and then steadily increased up to December 2020, reaching 180% compared to previous years, with double the number of outpatient appointments compared to previous years.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, many services were provided by telephone or video contact (22). Revet et al estimated the impact of COVID-19 on child and adolescent psychiatry services in Europe and they reported that the perceived impact on the mental health and psychopathology of children and adolescents dramatically increased in 2020 and 2021 (11).…”
Section: Discussionmentioning
confidence: 99%
“…We used the classification we had often seen in other studies as we thought it was correct: small children (0-5 years), school children (6-12 years) and adolescents (13-17 years). However, we also further stratified 6-12-year-olds into two groups (6)(7)(8)(9)(10)(11)(12) as this makes a difference between children attending primary school (first 4 years) and those attending secondary school in Germany-primary schools were not closed for as long as secondary schools.…”
Section: Procedures and Outcomesmentioning
confidence: 99%
See 1 more Smart Citation